COMPARATIVE STUDY OF METHODS FOR CALCULATING IONOSPHERIC POINTS AND DESCRIBING THE GNSS SIGNAL PATH - Prol, Fabricio dos Santos; Camargo, Paulo de Oliveira; Muella, Marcio Tadeu de Assis Honorato (Boletim de Ciências Geodésicas, 2017)
Many efforts have been done in the last decades to improve the formulation of ionospheric models based on data derived from the Global Navigation Satellite System (GNSS). Despite significant improvements in estimating the electron content of the GNSS signal path, little attention has been given to the geometric precision of ionospheric points that describe the signal path. In this work, we show a pioneer comparison about the geometric quality of the ionospheric points using distinct methods. Such analysis was carried out by calculating the GNSS signal path through three methods: a well-known geometric formulation; a new method based on linear approximations; and the used by NeQuick and recommended by the International Telecommunication Union, which was used as reference. As a result, we verified that the mean error of the well-known formulation was about 0.7 km and for the new method was at the level of 10-11 km. Also, the proposed method has the advantage to enable the calculation of ionospheric points for GNSS signals with negative elevation angles. Once negative elevation angles derived from Radio-Occultation techniques are definitively important to improve the geometrical coverage of ionospheric modeling, the proposed technique can be useful in the development of ionospheric modeling processes.